The Meaning of Finance Minister Purbaya Yudhi Sadewa's Speech in the TikTok Video: A Semantic Study Perspective - Nahdliya Mutammimah (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to analyze the semantic meaning aspects contained in the utterances of Minister of Finance Purbaya Yudhi Sadewa in various TikTok videos uploaded between September and October 2025. This study focuses on four aspects of meaning according to Sumarti's (2017) theory, namely sense (understanding), feeling (feeling), tone (tone), and intention (purpose). The research method used is descriptive qualitative with listening and note-taking techniques. The data consists of Mr. Purbaya's verbal utterances when responding to various issues, such as fiscal policy, cigarette excise, and tax and customs services. The results of the analysis show that Mr. Purbaya's speech represents a straightforward, open, humorous, and down-to-earth communication style of public officials. The sense aspect displays conceptual meanings related to economic and fiscal policies; feeling shows feelings of confidence, empathy, and assertiveness; tone shows a relaxed, humorous, yet authoritative tone; while intention emphasizes the purpose of communication to build public trust and strengthen the image of a transparent government. This study concludes that the use of communicative and humanistic language styles can be an effective strategy in building relationships between public officials and the public.